2012
DOI: 10.1007/s00277-011-1397-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAPK activity promotes ex vivo expansion of human cord blood hematopoietic stem cells

Abstract: Ex vivo expansion of hematopoietic stem cells (HSCs) depends on HSC self-renewing proliferation and functional maintenance, which can be negatively affected by HSC differentiation, apoptosis, and senescence. Therefore, inhibition of HSC senescence may promote HSC expansion. To test this hypothesis, we examined the effect of inhibition of p38 mitogen-activated protein kinase (p38) on the expansion of human umbilical cord blood (hUCB) CD133+ cells because activation of p38 has been implicated in the induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
6
43
0
Order By: Relevance
“…As recently reported, the inactivation of p38 activity by small molecule inhibitors maintained stemness ex vivo in human and murine HSCs (Baudet et al, 2012;Zou et al, 2012). Furthermore, an increase in reactive oxygen species results in the activation of p38 and finally in HSC …”
Section: Discussionsupporting
confidence: 53%
“…As recently reported, the inactivation of p38 activity by small molecule inhibitors maintained stemness ex vivo in human and murine HSCs (Baudet et al, 2012;Zou et al, 2012). Furthermore, an increase in reactive oxygen species results in the activation of p38 and finally in HSC …”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, p38MAPK inhibition by SB203580 or by a dominant-negative form of Map3k5 (which phosphorylates and activates p38MAPK) reportedly rescued these HSC defects (Ito et al, 2006). In support of this idea, others reported that small hairpin RNA (shRNA) targeting Mapk14 or treatment with SB203580 promoted expansion of human cord blood HSCs in vivo and ex vivo (Baudet et al, 2012;Zou et al, 2012). Interestingly, p38MAPK is thought to function as both a positive and negative regulator of the cell cycle (Arthur and Ley, 2013;Ashwell, 2006;Grossi et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment with the antioxidant N-acetyl-L-cysteine (NAC) or a p38MAPK inhibitor rescues HSPC number and function in serial BMT or Atm À/À cells in mice (Ito et al, 2004;Ito et al, 2006). Also, Mapk14 knockdown or p38MAPK inhibition promotes proper cell-cycle progression following BMT or in exvivo-expanded HSPCs (Baudet et al, 2012;Zou et al, 2012). Thus, p38MAPK inhibition is thought to suppress aberrant HSPC proliferation and protect HSPCs from exhaustion or replicative senescence in stress settings or in the context of damage associated with aging (Geiger et al, 2013;Rossi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…42 Differentiation of HSCs during their expansion increases the process of cell aging and death, 43 but direct contact between the stem cells and microenvironment of the cell represents their essential role in hematopoiesis versus differentiation. 44 Mesenchymal stem cells produce a variety of cytokines and factors affecting hematopoiesis. 45,46 IL-6, Flt3-L (FL), SCF, G-CSF, M-CSF, GM-CSF, TPO, CXCL-12 (SDF1) and IL-11 are among these factors.…”
Section: Effect Of Msc On Differentiation Of Hscsmentioning
confidence: 99%